2015
DOI: 10.1590/0104-6632.20150321s00003120
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of 1-Butyl-3-Methylimidazolium Bis(trifluoromethylsulfonyl)imide at High Temperatures and Pressures

Abstract: -Pressure-density-temperature (p,ρ,T) data of the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][NTf 2 ] at T = (273.15 to 413.15) K and pressures up to p =140 MPa are reported with an estimated experimental relative combined standard uncertainty of Δρ/ρ = ±(0.01 to 0.08)% in density. The measurements were carried out with a newly constructed Anton-Paar DMA HPM vibration-tube densimeter. The system was calibrated using double-distilled water, aqueous NaCl solution, methanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 29 publications
5
36
0
Order By: Relevance
“…As illustration, we presented the comparison of density calculated by an indirect acoustic method as a function of pressure to ones measured directly by high pressure densimeter, as well as, speeds of sound and isentropic compressibilities reported in literature (Figures 25 and 26). 14,17,214,218 The results underscore previous warnings as to the enormous errors incurred by using the Safarov's approximation for calculation of high-pressure speed of sound data.…”
Section: Calculation Of Volumetric Properties and Thermodynamic Formamentioning
confidence: 55%
See 3 more Smart Citations
“…As illustration, we presented the comparison of density calculated by an indirect acoustic method as a function of pressure to ones measured directly by high pressure densimeter, as well as, speeds of sound and isentropic compressibilities reported in literature (Figures 25 and 26). 14,17,214,218 The results underscore previous warnings as to the enormous errors incurred by using the Safarov's approximation for calculation of high-pressure speed of sound data.…”
Section: Calculation Of Volumetric Properties and Thermodynamic Formamentioning
confidence: 55%
“…where N is the number of points of the data set considered. y1 -data reported by Dzida et al 214 , y2 -data reported by b Esperança et al 17 , c Gomes de Azevedo et al 14 , d Hamidova et al 218 , e Currás et al 286 , f Wojnarowska et al 287 and g Safarov et al 207…”
Section: Calculation Of Volumetric Properties and Thermodynamic Formamentioning
confidence: 94%
See 2 more Smart Citations
“…Ionic Liquids (ILs) are salts which are liquid below the boiling temperature of water, are based on ionic structures, very frequently having low vapor pressures at room temperature or below, normally featuring a high viscosity and potentially could be either hydrophobic or hydrophilic . As an example, 1‐ethyl‐3‐methylimidazolium ethylsulphate (EtOSO 3 ) has a melting point of 175 K. Furthermore they are non‐flammable, and commonly thermally stable over a wide range of temperatures . This would make them a suitable candidate for future space grade lubricants that seldom operate at temperatures lower than 230 K .…”
Section: Methodsmentioning
confidence: 99%